Medieval Boats from Nin: Wood Species Identification (Archaeologia Adriatica, 2010)
Two boats (Nin 1 and Nin 2) were discovered in the 1960s at the entrance to Nin harbor, fifteen km northwest of Zadar. In 1974 the boats were lifted from the sea bed, were preserved in PEG and presented to the public in the Museum of Nin Heritage. According to radiocarbon evidence the boats date to the eleventh/twelfth century. They were about 8 m long and were built in skeleton first technique. The frames and planks were fastened together with nails and treenails. Instead of a central keel they were provided with a keel plank and two parallel bilge keels, which run below the garboards. A wooden base for the mast step was also found. A sampling of the wooden elements to identify wood species was realized in 2008. Sixty-one samples were taken from various elements of the Nin 1 frames, futtocks, stem post, bilge keel, planks and central plank), and 91 samples were taken from Nin 2 (frames, planks, bilge keel and central plank). The majority of the components from both wrecks were made of Quercus petraea. In Nin 1, 43 of 61 samples were of Quercus petraea, and 12 samples were of Quercus cerris. One plank was made of Platanus orientalis, another of Ulmus campestris. Four analyzed components were identified as Abies alba and are probably modern insertions in the reconstruction. In Nin 2, 84 of 91 samples were made of Quercus petraea, 6 of Quercus cerris. One plank was identified as Ulmus campestris. The native distribution area of Quercus petraea and Quercus cerris coincide. Both oak species are very common in Croatia and the Balkans. Anatomical features indicate that both species of oak that were used as construction timber for the Nin boats grew in a region characterized by high mountains and very cold winters, resulting in trees which are better fit for shipbuilding because of their strength and lack of insect and fungal damage. While it is logical to assume that local boatyards building small boats would have exploited local timber sources, or whatever was locally available, it is possible that such timbers were depleted in this region, thus forcing the procurement of timber from mountainous areas.
Keywords: boat; Middle Ages; underwater excavation; dendrological analysis; nautical archaeology